Sequencing effects of neuromuscular training on physical fitness in youth elite tennis players - Fernandez-Fernandez, J.; Granacher, U.; Sanz-Rivas, D.; Sarabia Marin, J. M.; Hernandez-Davo, J. L.; Moya, M. (The Journal of Strength and Conditioning Research, 2018)
The aim of this study was to analyze the effects of a 5-week neuromuscular training (NMT) implemented before or after a tennis session in prepubertal players on selected components of physical fitness. Sixteen high-level tennis players with a mean age of 12.9 ± 0.4 years participated in this study, and were assigned to either a training group performing NMT before tennis-specific training (BT; n = 8) or a group that conducted NMT after tennis-specific training (AT; n = 8). Pretest and posttest included: speed (5, 10, and 20 m); modified 5-0-5 agility test; countermovement jump (CMJ); overhead medicine ball throw (MBT); and serve velocity (SV). Results showed that the BT group achieved positive effects from pretest to posttest measures in speed (d = 0.52, 0.32, and 1.08 for 5, 10, and 20 m respectively), 5-0-5 (d = 0.22), CMJ (d = 0.29), MBT (d = 0.51), and SV (d = 0.32), whereas trivial (10 m, 20 m, CMJ, SV, and MBT) or negative effects (d = -0.19 and -0.24 for 5 m and 5-0-5, respectively) were reported for the AT group. The inclusion of an NMT session before the regular tennis training led to positive effects from pretest to posttest measures in performance-related variables (i.e., jump, sprint, change of direction capacity, as well as upper-body power), whereas conducting the same exercise sessions after the regular tennis training was not accompanied by the same improvements.